PERLAKUKAN KHUSUS TERHADAP NARAPIDANA DISABILITAS UPAYA MEMENUHI KESEJAHTERAAN KELOMPOK RENTAN DI LEMBAGA PEMASYARAKATAN - Dhini Annissa Silalahi; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
Prisoners with disabilities are a vulnerable group who need to get special treatment while serving prison sentences, this group can show declining physical and mental abilities. Poor physical and mental health results in the activities undertaken in prison being unproductive and dependent on other people. Efforts to realize human rights-based treatment of prisoners with disabilities and the elderly as outlined in statutory regulations, namely Law Number 8 of 2016. Correctional Institutions are a place of guidance for those who are convicted, prisoners only do not get freedom of movement and still get human rights Humans are supposed to be and this is fulfilled by Correctional Institutions. Rights that they should have such as special residential rooms, special lanes for disabilities, and wheelchairs and canes to facilitate movement as a form of fulfilling the social welfare of vulnerable groups. Therefore, this article uses a normative procedure that is intended to study by studying literature and secondary materials such as related laws and regulations. The results of the research state that if the fulfillment of the rights of prisoners with disabilities in prisons is still not optimal, it is necessary to evaluate and improve the quality of trials by prisons and other agencies related to this matter, and not only that, further regulations are also needed that focus on guaranteeing rights for prisoners with disabilities.